2020
DOI: 10.1370/afm.2478
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Survival of Older Patients With Dizziness in Primary Care: A 10-Year Prospective Cohort Study

Abstract: PURPOSE The prognosis of older patients with dizziness in primary care is unknown. Our objective was to determine the prognosis and survival of patients with different subtypes and causes of dizziness. METHODS In a primary care prospective cohort study, 417 older adults with dizziness (mean age 79 years) received a full diagnostic workup in 2006-2008. A panel of physicians classified the subtype and primary cause of dizziness. Main outcome measures were mortality and dizziness-related impairment assessed at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Dizziness tends to be more common with increasing age as well as with higher morbidity and may well be a sign associated with morbidity, also in younger ages [ 5 ]. Having dizziness, non-vertigo type, has been associated with higher mortality risk, compared to dizziness due to peripheral causes [ 38 ]. The most common duration of dizziness was seconds and symptoms triggered by raising up or by positional changes, symptoms often seen in orthostatic hypotension or benign paroxysmal positional vertigo (BPPV).…”
Section: Discussionmentioning
confidence: 99%
“…Dizziness tends to be more common with increasing age as well as with higher morbidity and may well be a sign associated with morbidity, also in younger ages [ 5 ]. Having dizziness, non-vertigo type, has been associated with higher mortality risk, compared to dizziness due to peripheral causes [ 38 ]. The most common duration of dizziness was seconds and symptoms triggered by raising up or by positional changes, symptoms often seen in orthostatic hypotension or benign paroxysmal positional vertigo (BPPV).…”
Section: Discussionmentioning
confidence: 99%
“…15 Although spinning vertigo was associated with reduced risk of mortality after adjusting for age, sex, and comorbidities, it failed to reach significance in the final model (stepwise inclusion) when other symptom characteristics, including timing, were included. Van Vugt and colleagues found vertigo to be associated with a more favorable outcome than other types of dizziness among elderly patients in primary care, 5 whereas Newman-Toker and colleagues found that the type of dizziness was inconsistently reported by patients in an emergency department. 6 Our findings indicated that the time course of symptoms such as short attacks or episodic dizziness was more relevant to survival than the quality of symptoms, such as spinning vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct treatable vestibular disease entities, dizziness caused by medication, cardiovascular disease or diabetes may align with symptoms of the ageing of vestibular, proprioceptive or somatosensory systems. Therefore, a considerable percentage of older adults with confirmed vestibular vertigo experience limited functioning and impairment in their health-related quality of life (HRQoL) due to their untreated VDB [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%